Chińskie imperium ratuje euroland przed kryzysem - Cywoniuk, Justyna (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2012)
Since 2007 the world has been dealing with financial and economic crisis. From that moment a period of enormous loans for indebted countries, especially for PIGS countries, has started. It is also the period of budget savings within the social, pension and wage area. Workers’ enslavement and a high unemployment rate caused mass demonstrations spreading from one neighboring country to another. The only solution to stabilize the situation in many countries was the infusion of an enormous amount of money in order to deal with multibillion debt. That is why, the EU has decided to help the European economies and the Euro zone. There has also been a real need for a bigger bailout. China has turned out to be a country that helped and stimulated many EU economies. The Asian country has given the financial support to countries belonging to PIGS. What is more, thanks to some investments China has started an ‘economic invasion’ in Europe. However, Chinese help is not disinteresting as it wants to achieve some political goals.
A Chinese Empire Saves Euro Zone From Crisis
Keywords: Chiny; Unia Europejska; Kryzys ekonomiczny; Pomoc finansowa